2018
DOI: 10.1080/10408398.2018.1491828
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of 7-ketocholesterol-induced side effects by natural compounds

Abstract: Cholesterol oxidation products, also named oxysterols, can be formed either by cholesterol auto-oxidation, enzymatically or both. Among these oxysterols, 7-ketocholesterol (7KC) is mainly formed during radical attacks that take place on the carbon 7 of cholesterol. As increased levels of 7KC have been found in the tissues, plasma and/or cerebrospinal fluid of patients with major diseases, especially age-related diseases (cardiovascular diseases, eye diseases, neurodegenerative diseases), some cancers, and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 196 publications
4
59
0
1
Order By: Relevance
“…Our results support observations done in different cells exposed to other cytotoxic oxysterols (24(S)-hydroxycholesterol and 7 kC), which demonstrate that the alteration of cholesterol synthesis is associated with mitochondrial dysfunction leading different forms of cell death including apoptosis and necroptosis [51,92]. The alteration of cholesterol synthesis could contribute to the demyelination process and defects in the quality of myelin [29]. Cholesterol can also be oxidized, leading to the formation of 7 kC and 7b-OHC [93].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results support observations done in different cells exposed to other cytotoxic oxysterols (24(S)-hydroxycholesterol and 7 kC), which demonstrate that the alteration of cholesterol synthesis is associated with mitochondrial dysfunction leading different forms of cell death including apoptosis and necroptosis [51,92]. The alteration of cholesterol synthesis could contribute to the demyelination process and defects in the quality of myelin [29]. Cholesterol can also be oxidized, leading to the formation of 7 kC and 7b-OHC [93].…”
Section: Discussionsupporting
confidence: 90%
“…To oppose the deleterious effect of 7b-OHC, different strategies can be proposed, they can consist of either (i) degrading 7b-OHC and/or (ii) inactivating it via sulfonation or esterification with specific enzymes and/or (iii) inhibiting its signalling pathways leading to side effects with natural or synthetic molecules [29]. At the moment, a-tocopherol (the major component of vitamin E) and docosahexaenoic acid (DHA, C22:6 n-3) are the only molecules that can attenuate the noxious effects of 7b-OHC [24,30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when their concentration is abnormal, oxysterols are associated with demyelinating or neurodegenerative diseases such as Parkinson's or Alzheimer's disease [108,109]. 7-ketocholesterol (7KC) is capable of inducing cell death and oxidative stress in 158N oligodendrocyte cells [110].…”
Section: Cytoprotector Effects Of Vegetable Oilmentioning
confidence: 99%
“…This accumulation of oxysterols in myelin figures has been considered first as a phospholipidosis process to attenuate the cytotoxic effects of oxysterols. It is now suggested that these myelin figures could also include autophagic vesicles (resulting from reticulophagy) involving the fusion of the autophagosome, containing large parts of endoplasmic reticulum, within the lysosome [98]. It is suggested that the process of phospholipidosis would prevent the intracellular accumulation of 7KC which favours lysosomal membrane destabilization and contributes to cell death induction [97].…”
Section: 5-oxysterols and Lysosomesmentioning
confidence: 99%